Prevalence and risk factors for gastric ulceration in pigs slaughtered at 170 kg. (24th April 2017) - Gottardo, F.; Scollo, A.; Contiero, B.; Bottacini, M.; Mazzoni, C.; Edwards, S. A.
Abstract : Oesophago-gastric ulcers (OGU) are a production and welfare problem in pigs. Stomach condition was scored for 22 551 pigs in 228 batches over a 7-month period at an abattoir in Italy processing heavy pigs for ham production. Mild or severe ulceration was observed in 20.7% of pigs, of which 13% had scar tissue. Variation between batches was high (0% to 36% prevalence of severe ulcers) and showed a significant effect of farm of origin ( P <0.001). Overnight lairage increased the prevalence of mild ulcers ( P <0.001), but not severe or scarred ulcers. Scarred ulcers increased in the hottest summer months. Prevalence of ulcers showed only few and weak correlations at batch level with pathologies of the pleura, lungs and liver, but a strong correlation with on-farm mortality of the batch. Analysis of farm risk factors for OGU was assessed by questionnaire with a response rate of 17% of farms. Risk factors retained in a multivariable model included a protective effect of anthelmintic treatment (risk ratio (RR)=5.1, P =0.03), increased risk in farms using Mycoplasma vaccination (RR=5.6, P =0.04) and a tendency for association with type of flooring ( P =0.06). Univariable analyses also highlighted possible influences of other stress-inducing factors including lack of enrichment objects and mixing of pigs during fattening, suggesting that the role of on-farm stressors merits further investigation. It is concluded that abattoir screening of OGU in future programmes for the assessment of well-being on farm should encompass only severe lesions and scarring, and results be returned to farmers to facilitate improvement of production and welfare.